German network for congenital Uro-REctal malformations: first evaluation and interpretation of postoperative urological complications in anorectal malformations - Märzheuser, Stefanie; Jenetzky, Ekkehart; Zwink, Nadine; Reutter, Heiko; Bartels, Enrika; Grasshoff-Derr, Sabine; Holland-Cunz, Stefan; Hosie, Stuart; Schmiedeke, Eberhard; Schwarzer, Nicole; Spychalski, Nicole; Goetz, Gabriel; et al. (Pediatric surgery international, 2011)
The aim of the German Network for Congenital Uro-REctal Malformations is to collect data of affected patients with anorectal malformation (ARM) or extrophy-epispadias complex, and to investigate molecular causes, clinical implications, and psychosocial outcome. The current issue was to assess the postoperative sequelae related to lower urinary tract dysfunction in patients with ARM.
Gesehen am 25.11.2022